Diel Infection of Cyanobacteria by Cyanophages - Ni, Tianchi; Zeng, Qinglu (Frontiers in Marine Science, 2016)
Cyanobacteria exhibit biological rhythms as an adaptation to the daily light-dark (diel) cycle. Light is also crucial for bacteriophages (cyanophages) that infect cyanobacteria. As the first step of infection, the adsorption of some cyanophages to their host cells is light-dependent. Moreover, cyanophage replication is affected by light intensity and possibly the host cell cycle. Photosynthesis and carbon metabolism genes have been found in cyanophage genomes. With these genes, cyanophages may affect the host metabolic rhythm. Field studies suggest that cyanophage infection of cyanobacteria in aquatic environments is synchronized directly or indirectly to the light-dark cycle. These discoveries are beginning to reveal how the daily light-dark cycle shapes the interaction of cyanophages and cyanobacteria, which eventually influences matter and energy transformation in aquatic environments.